Validation of Persian Version of the Telephone Interview for Cognitive Status-modified Questionnaire Among Iranian Adults - Aminisani N; Shamshirgaran M; Laghousi D; Javadpour A; Gholamnezhad Z; Gilani N; Alpass F (Mazandaran University of Medical Sciences and Health Services, 2022)
Background: Dementia is a growing public health problem worldwide, and its early detection can help to manage the disease more effectively. This study aimed to validate the Persian version of the Telephone Interview for Cognitive Status-modified (TICS-m) questionnaire in older adults in the northeast of Iran. Methods: This cross-sectional study was accomplished as part of the Neyshabur Longitudinal Study on Ageing (NeLSA) from January to May 2019. The translated Persian version of TICS-m was tested for content and face validity. The construct validity of the questionnaire was also assessed using exploratory factor analysis (EFA) with the extraction method of principal component analysis (PCA) and Oblimin rotation. Results: A total of 210 community-dwelling adults (aged ≥ 50; mean age: 59.6 ± 6.8 years) were registered in the NeLSA. The content validity ratio (CVR) of all items in the TICS-m questionnaire was higher than 0.62. The content validity index (CVI) of the three items was less than 0.78; so, these items were revised and replaced with alternative words. The face validity of the questionnaire was also confirmed. According to the results of EFA, the six extracted factors accounted for 68.8% of the total variance. Conclusions: Our results revealed that the construct validity of the Persian version of the TICS-m is satisfactory.